Hemodynamic Study of Stanford Type B Aortic Dissection Based on Ex Vivo Porcine Aorta Models. (June 2023) - Liang, Shichao; Jia, Heyue; Dong, Huiwu; Li, Zhenfeng; Zhou, Guojing; Zhang, Xuehuan; Chen, Duanduan; Xiong, Jiang
Background: In this study, we aimed to evaluate hemodynamic influence of the dissected aortic system via various ex vivo type B aortic dissection (AD) models. Methods: Twenty-four raw porcine aortas were harvested and randomly divided into 4 groups to create various aortic models. Model A was the control group, while models B to D indicated the AD group, where models B and C presented a proximal primary entry with the false lumen (FL) lengths of 15 and 20 cm, respectively, and model D presented a 20 cm FL with a proximal primary entry and a distal reentry. All the aortic models were connected to a mock circulation loop to attain the realistic flow and pressure status. The flow distribution rate (FDR) of the aortic branches was calculated. Doppler ultrasound was applied to visualize the AD structure and to attain the velocity of flow in both the true and false lumens. Several sections of the AD were stained with hematoxylin and eosin for histologic evaluation after the experiment. Results: This study demonstrated that higher pressures were found for the AD group compared with the control group. The mean systolic pressures at the inlet of models A to D were 113.34±0.81, 120.58±0.52, 117.76±0.82, and 115.87±0.42 mm Hg, respectively. The FDRs of the celiac artery in models A to D were 8.65%, 8.32%±0.15%, 7.87%±0.13%, and 8.03%±0.21%, respectively. By ultrasound visualization, the velocity of the flow at the entry to the FL in the AD group ranged in 10 to 92 cm/s. The dissection flap presented pulsatile movement, especially in the models B and C which contained 1 primary entry without distal reentries. Histological examinations indicated that AD was located between the intimal and medial layers. Conclusions: Our ex vivo models demonstrated that the configuration of the dissected aorta influenced the pressure distribution. Moreover, the dissection flap affected the FDR of the aortic branches that possibly inducing malperfusion syndrome.